Human-Computer Interaction: A Review of the Research on its Affective and Social Aspects - Deaudelin, Colette; Dussault, Marc; Brodeur, Monique (Canadian Journal of Learning and Technology, 2003)
Prevailing research influenced by cognitive psychology has dealt mainly with the cognitive aspects of the human-computer interaction (HCI). The advent of computers in schools should prompt educational researchers to scrutinize the affective and social aspects of student-computer interactions since they play an important role in learning. A review of 34 qualitative and non-qualitative studies was conducted. Its main purpose is to synthesize results and to highlight important issues that research has left unsolved. Results concern the nature of the HCI (social or parasocial), the interface (mainly a comparison between graphic and text types), and the relation between variables linked to HCI (mainly trust, locus of control, attitude, ease of use, and liking).